Voyages en Shangrila : le marché « in situ » des objets d’art primitif d’Himalaya - Gisèle Krauskopff (Ateliers d'Anthropologie)
In the early 1990s, collector catalogues and exhibitions established a new aesthetic genre, Himalayan primitive art. Studying the local market in Kathmandu—birthplace of these objects in the 1970s—makes it possible to show the market context in which they were selected, exchanged and classified, revealing the role that tourism and hippy travellers play in their circulation. The market is a site of negotiation, but also a “cultural constellation”. The article examines the conditions underlying the production of the narratives that transformed these artefacts into “art objects” and stripped them of the market conditions behind their discovery. It studies the mediums of these narratives, exhibitions, sales catalogues and collector catalogues that developed these objects’ narratives of origins, as well as the “aura” that helps them gain recognition on the primitive art market. Between Buddhist transcendence and primordial shamanism, this myth of origin sketches a utopian landscape, mediated by art objects. This journey back to where these objects were negotiated shows how classificatory reconfigurations operate, first on the local market and then in Western galleries, and the role played by dealers and collectors in the birth of a Himalayan primitive art.